Shariah Bank Fundamental, Maqashid and Financial Sustainability: Unraveling the Dynamics - Wiyawan, Dego; Hendrawati, Hendrawati; Burda, Agustian; Merliyana, Merliyana; Saefurahman, Asep (Research of Islamic Economics, 2024)
The purpose of this study is to ascertain how the Financial Sustainability Ratio in Indonesian Sharia Commercial Banks is impacted by Return on Assets, Firm Size, Capital Adequacy Ratio, and Maqashid Syariah. This study employs a quantitative method along with a causal research technique. This study makes use of financial report data from 15 Sharia Commercial Banks as its population. Fifteen Indonesian Sharia Commercial Banks were the sample used for the 2017–2022 research period. The Panel Data Regression Analysis approach is used in this study. This research uses a population of 15 Sharia Commercial Banks using financial report data. The sample used was 15 Sharia Commercial Banks in Indonesia, which served as research subjects from 2017 to 2022. The Panel Data Regression Analysis approach is used in this study. Based on the findings and discussion, it is evident that the Financial Sustainability Ratio of Indonesia's Sharia Commercial Banks is significantly influenced by Return on Assets, not significantly influenced by Maqashid Syariah, significantly impacted by Firm Size, and significantly impacted by Capital Adequacy Ratio (CAR). Managerial implications include efforts to strengthen financial practices based on Sharia payment principles, considering asset returns, Sharia mashed, company size, and capital adequacy ratios.